The Role of Social Media and Online Reviews in Building Brand Loyalty Through Trust - Nurul Amalia Fitriyana; Nanang Suryadi; Raditha Dwi Vata Hapsari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of the local skincare industry in Indonesia has highlighted the importance of digital marketing strategies in building consumer loyalty. This study aims to examine the relationships among social media marketing activity, online customer reviews, brand trust, and brand loyalty in the context of local skincare brands such as Wardah, MS Glow, and Somethinc. A quantitative approach was employed, using a structured questionnaire to collect data from 170 consumers aged 17 and above who use these brands. The data were analyzed using partial least squares structural equation modeling to test the hypothesized relationships. The findings reveal that online customer reviews have a direct and significant impact on brand loyalty, while social media marketing activity influences loyalty indirectly through its effect on brand trust. Both social media marketing activity and online customer reviews significantly enhance brand trust, which in turn fosters brand loyalty. The study concludes that local skincare brands should prioritize managing online reviews and creating authentic social media content to build trust and loyalty. These insights offer practical strategies for brand managers to strengthen consumer relationships in a competitive digital market.